Comparing the Impact of Laparoscopic Sleeve Gastrectomy and Gastric Cancer Surgery on Resting-State Brain Activity and Functional Connectivity - Gu, Yong; Li, Guanya; Wang, Jia; von Deneen, Karen M.; Wu, Kaichun; Yang, Yan; She, Junjun; Ji, Gang; Nie, Yongzhan; Cui, Guangbin; Zhang, Yi; He, Shuixiang (Frontiers in Neuroscience, 2020)
Laparoscopic sleeve gastrectomy (LSG) is one of the most performed bariatric surgeries in clinical practice. Growing neuroimaging evidence shows that LSG induces brain functional and structural alterations accompany with sustained weight-loss. Meanwhile, for clinical treatment of gastric cancer, stomach removal surgery is a similar procedure to LSG. It is unclear if the gastric cancer surgery (GCS) would induce the similar alterations in brain functions and structures as LSG, and it would help to clarify the specificity of the LSG. We recruited 24 obese patients who received LSG in the LSG group and 16 normal weight patients with gastric cancer who received GCS as the control group. Functional magnetic resonance imaging was employed to investigate the differences and similarity of surgery’s impact on resting-state brain activity and functional connectivity (RSFC) between LSG and GCS groups. Both LSG and GCS groups showed increased activities in the posterior cingulate cortex (PCC) and supplementary motor area (SMA) as well as the decreased RSFC of PCC- dorsomedial prefrontal cortex and SMA- dorsolateral prefrontal cortex. There were decreased resting-state activity of hippocampus and putamen in LSG group and increases in GCS group. In LSG group, resting-state activities of hippocampus and putamen were correlated with craving for high-caloric food and body mass index after surgery, respectively. These findings suggest LSG induced alterations in resting-state activity and RSFC of hippocampus and putamen specifically regulate the obese state and overeating behaviors in obese patients.